Abnormalities in Electroencephalographic Microstates Among Adolescents With First Episode Major Depressive Disorder - He, Yuqiong; Yu, Qianting; Yang, Tingyu; Zhang, Yaru; Zhang, Kun; Jin, Xingyue; Wu, Shuxian; Gao, Xueping; Huang, Chunxiang; Cui, Xilong; Luo, Xuerong (Frontiers in Psychiatry, 2021)
Background: Recent studies have reported changes in the electroencephalograms (EEG) of patients with major depressive disorder (MDD). However, little research has explored EEG differences between adolescents with MDD and healthy controls, particularly EEG microstates differences. The aim of the current study was to characterize EEG microstate activity in adolescents with MDD and healthy controls (HCs). Methods: A total of 35 adolescents with MDD and 35 HCs were recruited in this study. The depressive symptoms were assessed by Hamilton Depression Scale (HAMD) and Children’s Depression Inventory (CDI), and the anxiety symptoms were assessed by Chinese version of DSM-5 Level 2-Anxiety-Child scale. A 64-channel EEG was recorded for 5 minutes (eye closed, resting-state) and analyzed using microstate analysis. Microstate properties were compared between groups and correlated with patients’ depression scores. Results: We found increased occurrence and contribution of microstate B in MDD patients compared to HCs, and decreased occurrence and contribution of microstate D in MDD patients compared to HCs. Furthermore, microstate B contribution and transition from microstate ‘C to B’ were correlated with HAMD scores. Conclusions: Adolescents with MDD showed microstate B and microstate D changes, and the microstate B contribution was related to depression symptoms. The obtained results may deepen our understanding of dynamic EEG changes among adolescents with MDD and provide some evidence of changes in brain development in adolescents with MDD.